Meneroka Strategi Daya Tindak Golongan Ibu dalam Menjaga Anak Kurang Upaya Kategori Cerebral Palsy (Exploring Coping Strategies of Mother in Taking Care of a Child with Cerebral Palsy Disability) - Tharshini, A/P Sivabalan; Ezarina, Zakaria; Aizan Sofia, Amin (Penerbit UKM, 2018)
Living with a disabled person can bring significant effects to the entire family members especially for parents, siblings and next of kin because they need to undergo a peculiar experience which can influence different aspect of family functioning. Thus, this article examines coping strategies of mothers who take care of their child with Cerebral Palsy disability. Data is collected using a qualitative approach among six mothers who have a child with Cerebral Palsy disability. In-depth interview was conducted to gather information regarding informants’ coping strategies in taking care of their children. All the informants who took part in this study were mothers in the age range between 33 to 52 years old with an average income rate between RM1,200 to RM3,000 and have two to three children. The findings also indicate that informants’ practiced four types of coping strategies namely; (i) self-control, (ii) social support, (iii) accepting responsibilities and (iv) solving problems with a proper planning in overcoming stress and crisis in their life. As an overall impact, the study provided implications to the concerned parties to empower and emancipate mothers by providing effective psychological counselling to overcome challenges in taking care of their disabled child.